las actividades lúdicas como herramienta para el aprendizaje del color en niños de preparatoria de la unidad educativa Cotaló, provincia de Tungurahua” - Llamuca Maigua, Monica Jacqueline (2018)
The objective of the research was to strengthen the learning of color in high school children through a guide of playful activities adapted to color. The methodology used was based on a mixed approach,that is to say qualitative - quantitative, with a descriptive scope, evaluating 22 children through questionnaires prepared by experts to diagnose their knowledge of color. In addition, a guide of playful activities adapted to color was applied to strengthen knowledge. Of the total number of children evaluated, 67% have increased their ability to identify colors, compared to their first diagnosis. Finally, the hypothesis was verified: The playful activities if significantly reinforce the learning of color in children’s post initial education in Cotaló’s School, where by means of a t-student test it was corroborated that the P value (t of two tails) is lower to 0.05, accepting the alternative hypothesis. In conclusion, recreational activities adapted as a learning tool, enhance the acquisition of knowledge of high school children. Key words: Playful activities, learning, color learning, playful activities guide